2021
DOI: 10.35530/it.072.04.1802
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of heat transfer and factors affecting the thermal propertieson rib 1x1 knitwear

Abstract: Clothing comfort is very important feature which is considered as a result of different process of heat exchange between human body, clothing and environment. The purpose of this paper is to analyse the impact of clothing insulation on the heat transfer. The measurements were carried out on commercially 1x1 RIB knitted fabrics used for the production of next-to-skin shirts. The one group of samples are made from 100% cotton yarn and another with 96% cotton and 4%lycra. It is noticed that knitted material compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This paper 18 demonstrated that once the fabric has been knitted, the loop length and width along with the shape that it takes in the fabric after each relaxation state will be the main factors responsible for fabric dimensional variations. Besides the dimensional stability of 1 × 1 rib knitted fabrics, their thermal 19 and mechanical 20,21 properties were also examined. Pešić et al 19 found a significant correlation between the bleached and dyed cotton and cotton/Lycra fabric thermal resistance and different fabric parameters like thickness, covering factor, and the surface coefficient.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper 18 demonstrated that once the fabric has been knitted, the loop length and width along with the shape that it takes in the fabric after each relaxation state will be the main factors responsible for fabric dimensional variations. Besides the dimensional stability of 1 × 1 rib knitted fabrics, their thermal 19 and mechanical 20,21 properties were also examined. Pešić et al 19 found a significant correlation between the bleached and dyed cotton and cotton/Lycra fabric thermal resistance and different fabric parameters like thickness, covering factor, and the surface coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the dimensional stability of 1 × 1 rib knitted fabrics, their thermal 19 and mechanical 20,21 properties were also examined. Pešić et al 19 found a significant correlation between the bleached and dyed cotton and cotton/Lycra fabric thermal resistance and different fabric parameters like thickness, covering factor, and the surface coefficient. 1 × 1 rib knitted fabrics having Lycra in their compositions were more compact and possessed higher heat resistance than 100% cotton fabrics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation